Narrativity and enaction: the social nature of literary narrative understanding - Popova, Yanna B. (Frontiers in Psychology, 2014)
This paper proposes an understanding of literary narrative as a form of social cognition and situates the study of such narratives in relation to the new comprehensive approach to human cognition, enaction. The particular form of enactive cognition that narrative understanding is proposed to depend on is that of participatory sense-making, as developed in the work of Di Paolo and De Jaegher. Currently there is no consensus as to what makes a good literary narrative, how it is understood, and why it plays such an irreplaceable role in human experience. The proposal thus identifies a gap in the existing research on narrative by describing narrative as a form of intersubjective process of sense-making between two agents, a teller and a reader. It argues that making sense of narrative literature is an interactional process of co-constructing a story-world with a narrator. Such an understanding of narrative makes a decisive break with both text-centered approaches that have dominated both structuralist and early cognitivist study of narrative, as well as pragmatic communicative ones that view narrative as a form of linguistic implicature. The interactive experience that narrative affords and necessitates at the same time, I argue, serves to highlight the active yet cooperative and communal nature of human sociality, expressed in the many forms than human beings interact in, including literary ones.